2015
DOI: 10.1159/000430223
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization and Expression Analysis of Kv1.3 Potassium Channel in Primary Human Leukemic B Cells

Abstract: Background/Aims: Pharmacological inhibition of the potassium channel Kv1.3 has been shown to selectively kill B cells from patients with chronic lymphocytic leukemia (B-CLL). Here we aimed to biophysically characterize and compare Kv1.3 channel activity in B cells isolated either from healthy subjects or patients and investigated the mechanism accounting for the increased protein expression in B-CLL cells. Methods: Kv1.3 activity was measured by patch clamp, while expression of the channel protein was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 50 publications
5
29
0
Order By: Relevance
“…Consistent with these findings, it has been reported that cell apoptosis induced by radiation is regulated by a complex balance between pro-apoptotic factors, including caspase-3, c-caspase-3 and Bax, and anti-apoptotic factors, including the Bcl-2 family [71,72]. Recently, it has been shown that induction of apoptosis in T cells was associated with imbalance activation of caspase and Bcl-2 [73][74][75]. In the present study, we observed that TQ reduced radiation-induced caspase-3 and Bax activation and enhanced Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with these findings, it has been reported that cell apoptosis induced by radiation is regulated by a complex balance between pro-apoptotic factors, including caspase-3, c-caspase-3 and Bax, and anti-apoptotic factors, including the Bcl-2 family [71,72]. Recently, it has been shown that induction of apoptosis in T cells was associated with imbalance activation of caspase and Bcl-2 [73][74][75]. In the present study, we observed that TQ reduced radiation-induced caspase-3 and Bax activation and enhanced Bcl-2 expression.…”
Section: Discussionsupporting
confidence: 55%
“…In healthy individuals Kv1.3 is prevalently expressed mainly in the CNS and in immune cells [14]. Aberrant (mostly high) expression of Kv1.3 has instead been observed in different types of tumors [13, 15], such as melanoma [16], prostate [17], breast [18], B-cell lymphoma [19], chronic lymphocytic leukemia (B-CLL) [20, 21] gastric [22], pancreatic tumor [23] and in lung cancer [24]. Overexpression of Kv1.3, like that of other Kv channels, in cancer cells could give an advantage to cancer cells enhancing tumorigenic processes such as proliferation, cell migration and metastasis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kv1.3 displays an altered expression level in various cancers (Arcangeli et al 2009 ; Comes et al 2015 ; Bielanska et al 2009 ), such as lymphoma (Alizadeh et al 2000 ), melanoma (Artym and Petty 2002 ), glioma (Preussat et al 2003 ), breast (Abdul et al 2003 ; Jang et al 2009 ), prostate (Abdul and Hoosein 2006 ), gastric (Lan et al 2005 ) and colon cancer (Abdul and Hoosein 2002 ). Kv1.3 was also shown to be present in the mitochondrial inner membrane; in particular, it has been shown to be expressed in the prostate and breast cancer cell lines PC3 and MCF-7, respectively, and lymphoma and leukemia cells in the mitochondria (Leanza et al 2013b ; Szabo et al 2015 ; Gulbins et al 2010 ).…”
Section: Mitochondrial Channelsmentioning
confidence: 99%
“…We then provided evidence that pharmacological inhibition of mitoKv1.3 by membrane permeant blockers, the psoralens Psora-4 and PAP-1, and the riminophenazine clofazimine, is sufficient to trigger apoptotic cell death in cancer cells but not in healthy ones (Leanza et al 2012a , 2013b , 2014a , Szabo et al 2015 ). Inhibition of mitoKv1.3 induced a block of the potassium flux into the mitochondria inducing mitochondrial membrane hyperpolarization followed by reduction of the respiratory chain complexes, which causes increased ROS production.…”
Section: Mitochondrial Channelsmentioning
confidence: 99%
See 1 more Smart Citation